Management of Globus Pharyngeus. (11th July 2013) - Kortequee, S.; Karkos, P. D.; Atkinson, H.; Sethi, N.; Sylvester, D. C.; Harar, R. S.; Sood, S.; Issing, W. J.
Abstract : Globus pharyngeus is a common ENT condition. This paper reviews the current evidence on globus and gives a rational guide to the management of patients with globus. The aetiology of globus is still unclear though most ENT surgeons believe that reflux whether acidic or not plays a significant role. Though proton pump inhibitors are used extensively in practice, there is little evidence to support their efficacy. Most patients with globus can be discharged after simple office investigations. The role of pepsin-induced laryngeal injury is an exciting concept that needs further study. Given the benign nature of globus pharyngeus, in most cases, reassurance rather than treatment or extensive investigation with rigid oesophagoscopy or contrast swallows is all that is needed. We need more research into the aetiology of globus.